l-arginine: effect on reperfusion injury after heart transplantation - Szabó, Gábor; Bährle-Szabó, Susanne; Bátkai, Sándor; Stumpf, Nicole; Dengler, Thomas; Zimmermann, Rainer Johannes; Vahl, Christian-Friedrich; Hagl, Siegfried (World journal of surgery, 1998)
Global myocardial ischemia and reperfusion injury play a major role in early postoperative myocardial graft dysfunction. The aim of the present study was to investigate the effects of the nitric oxide (NO) precursor l-arginine on myocardial and endothelial function after hypothermic ischemia and reperfusion in a heterotopic rat heart transplantation model. After 1 hour ischemic preservation, reperfusion was started after application of placebo (control, n= 12) or l-arginine (l-Arg 40 mg/kg, n= 12), a substrate of NO synthesis. Myocardial blood flow (MBF) was assessed by the hydrogen clearance method. An implanted balloon was used to obtain pressure-volume relations of the transplanted heart. Left ventricular developed pressure (LVDP), rate of pressure development (dP/dt), end-diastolic pressure (LVEDP), isovolumic relaxation constant (TE), and MBF were measured after 60 minutes and 24 hours of reperfusion. Endothelium-dependent vasodilatation in response to acetylcholine (ACh) and endothelium-independent vasodilatation in response to sodium nitroprusside (SNP) were also determined. After 1 hour the MBF was significantly higher in the l-Arg group (3.6 ± 0.6 vs. 1.9 ± 0.2 ml/min/g, p < 0.05). The l-Arg group showed better recovery of systolic function and myocardial relaxation (LVDP 106 ± 6 vs. 70 ± 7 mmHg, p < 0.05; maximal dP/dt 5145 ± 498 vs. 3410 ± 257 mmHg/s, p < 0.05; TE 12.1 ± 0.9 vs. 16.1 ± 1.5 ms, p < 0.05, at an intraventricular volume of 80 μl). LVEDP was similar in the two groups. After 24 hours no difference was found between the groups for basal MBF, LVP, dP/dt, TE, LVEDP, or the response of MBF to SNP. However, ACh led to a significantly higher increase in MBF in the l-Arg group (52 ± 8% vs. 29 ± 7%,p < 0.05). These results indicate that (1) NO donation improves myocardial and endothelial functional recovery during early reperfusion after heart transplantation; and (2) initial treatment with l-Arg has a persisting beneficial effect against reperfusion-induced graft coronary endothelial dysfunction during late reperfusion.